Stimulating effect of palmitate and insulin on cell migration and proliferation in PNT1A and PC3 prostate cells: Counteracting role of metformin - Landim, Breno C.; de Jesus, Mariana M.; Bosque, Beatriz P.; Zanon, Renata G.; da Silva, Claudio V.; Góes, Rejane M. [UNESP]; Ribeiro, Daniele L. (Wiley, 2018)
Background: A potential association between obesity and prostate cancer has been proposed. Metformin, an antidiabetes drug, has antiproliferative effects being proposed for cancer treatment. However, under intense proliferative stimulation conditions such as those found in obesity, its efficacy is still uncertain. Thus, we analyzed the effects of saturated fatty acid and/or insulin under high concentrations, with or without metformin, on the proliferation and migration of prostate cells. Methods: Human prostate epithelial cell lines non-tumor (PNT1A) and tumor (PC3) were treated with control media (DMEM, C), palmitate (100 µM, HF), and/or insulin (50 µU, HI) with or without metformin (100 µM) for 24 or 48 h. Results: Both PNT1A and PC3 cells had greater proliferation when treated with HF, while HI treatment stimulated only PNT1A. Metformin inhibited cell proliferation caused by HF in both cell lines, but it did not block the proliferative action of HI in PNT1A cells. PNT1A increased cell migration after all treatments, while only HF influenced PC3; metformin inhibited the migration stimulated by all obese microenvironments. Both HF and HI treatments in PNT1A and HF treatment in PC3 augmented vimentin expression, resulting in a higher epithelial-mesenchymal transition (which, in turn, could influence cell migration). Metformin inhibited vimentin expression in both normal and tumor cells. Although HF treatment had increased AMPK activation, it also increased the levels of activated ERK1/2, which could be responsible for high cell proliferation in both cell lines. In contrast, HI decreased AMPK activation in both cell lines, whereas it increased ERK1/2 levels in PNT1A and decreased them in PC3 (reflecting greater cell proliferation only in non-tumor cells). Metformin maintained high activation of AMPK and decreased ERK1/2 levels after HF in both cell lines and only after HI in PNT1A, which was able to decrease the cell proliferation triggered by these treatments. Conclusions: Higher concentrations of palmitate on PC3 cells and palmitate and insulin on PNT1A cells stimulate cellular activities that could favor cancer progression. Metformin inhibited most of these stimuli, showing the efficacy of this drug for cancer adjuvant therapy in obese patients (a group at increased risk for the development of prostrate cancer).
Keywords: insulin; metformin; migration; palmitate; proliferation; prostate